ORIENTALIS DAN AL-QUR’AN (Ignaz Golziher, W. Montgomery Watt, Richard Bell) - Hafiz Hamdi Nasution; Muthmainnah; Sulidar (4, 2026)
Abstrack Orientalist studies of the Qur'an are a crucial discourse in the development of Islamic studies in the West, spanning from the Middle Ages to the modern era. Orientalists such as Ignaz Goldziher, Richard Bell, and W. Montgomery Watt have viewed the Qur'an through a historical-critical approach that positions the sacred text of Islam as a product of Arab history and culture. This approach often stems from epistemological assumptions that differ from the beliefs of Muslims, particularly regarding the concepts of revelation, prophecy, and the transmission of the Qur'anic text. Consequently, many of the conclusions reached contradict mainstream Islamic theological views. This article aims to analyze these orientalist views on the Qur'an and examine the critical responses of Muslim scholars and scholars. This research employs a qualitative method with a literature review approach, examining orientalist works as well as classical and contemporary Islamic literature. The results demonstrate that orientalism has indeed made significant contributions to the development of academic methodologies, such as textual criticism and historical analysis. However, on the other hand, many orientalist studies are considered to contain epistemological bias and theological reduction, because they ignore the transcendental dimension of the Quran as divine revelation. Muslim scholars and scholars have responded to this with methodological critiques based on Islamic scholarly traditions, such as the science of tafsir (interpretation), the science of the Quran, and the science of hadith. This critique affirms the authenticity of the Quran and the consistency of the transmission of revelation from the time of the Prophet Muhammad (peace be upon him) to the present day. Therefore, this study emphasizes the importance of a critical and proportionate approach to orientalism, so that Quranic studies can continue to develop academically without losing their theological and spiritual foundations. Abstrak Kajian orientalis terhadap Al-Qur’an merupakan salah satu diskursus penting dalam perkembangan studi Islam di Barat yang telah berlangsung sejak abad pertengahan hingga era modern. Para orientalis seperti Ignaz Goldziher, Richard Bell, dan W. Montgomery Watt memandang Al-Qur’an melalui pendekatan historis-kritis yang menempatkan teks suci Islam sebagai produk sejarah dan budaya Arab. Pendekatan ini sering kali berangkat dari asumsi epistemologis yang berbeda dengan keyakinan umat Islam, khususnya terkait konsep wahyu, kenabian, dan transmisi teks Al-Qur’an. Oleh karena itu, tidak sedikit kesimpulan yang dihasilkan bertentangan dengan pandangan teologis Islam arus utama. Artikel ini bertujuan untuk menganalisis pandangan para orientalis tersebut terhadap Al-Qur’an sekaligus mengkaji respons kritis dari ulama dan cendekiawan Muslim. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi pustaka, dengan menelaah karya-karya orientalis serta literatur keislaman klasik dan kontemporer. Hasil kajian menunjukkan bahwa orientalisme memang memberikan kontribusi signifikan dalam pengembangan metodologi akademik, seperti kritik teks dan analisis historis. Namun, di sisi lain, banyak kajian orientalis dinilai mengandung bias epistemologis dan reduksi teologis, karena mengabaikan dimensi transendental Al-Qur’an sebagai wahyu ilahi. Ulama dan cendekiawan Muslim merespons hal tersebut dengan kritik metodologis yang berlandaskan tradisi keilmuan Islam, seperti ilmu tafsir, ulumul Qur’an, dan ilmu hadis. Kritik ini menegaskan keotentikan Al-Qur’an serta konsistensi transmisi wahyu dari masa Nabi Muhammad SAW hingga kini. Dengan demikian, kajian ini menekankan pentingnya sikap kritis dan proporsional dalam menyikapi orientalisme, agar studi Al-Qur’an dapat terus berkembang secara akademik tanpa kehilangan landasan teologis dan spiritualnya.